2019
DOI: 10.1017/s0007114519001648
|View full text |Cite|
|
Sign up to set email alerts
|

dl-Methionine supplementation in a low-fishmeal diet affects the TOR/S6K pathway by stimulating ASCT2 amino acid transporter and insulin-like growth factor-I in the dorsal muscle of juvenile cobia (Rachycentron canadum)

Abstract: An 8-week feeding experiment was conducted to investigate the effects of dl-methionine (Met) supplementation in a low-fishmeal diet on growth, key gene expressions of amino acid transporters and target of rapamycin (TOR) pathway in juvenile cobia, Rachycentron canadum. Seven isonitrogenous and isolipidic diets were formulated, containing 0·72, 0·90, 1·00, 1·24, 1·41, 1·63 and 1·86 % Met. Weight gain and specific growth rates increased gradually with Met levels of up to 1·24 % and then decreased gradually. In d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 62 publications
4
13
1
Order By: Relevance
“…Our current observations indicated that optimal Met level elevated muscle TOR mRNA abundance, the total and phosphorylation of TOR protein levels of on-growing grass carp. These results were consistent with reports in cobia Rachycentron canadum (56) , songpu mirror carp (57) and broiler (58) demonstrating that Met could increase TOR (mTOR) mRNA abundance in the muscle, as well as in grass carp (59) , showing that Met could advance the protein levels of total and phosphorylated TOR in the intestine. Also, we found that optimal Met level reduced the ratio of p-TOR Ser2448 /t-TOR in the current experiment, which was inconsistent with that in cobia (56) and turbot Scophthalmus maximus L. (60) .…”
Section: Methionine Promoted the Deposition Of Nutrients In The Muscle Of Fishsupporting
confidence: 93%
See 1 more Smart Citation
“…Our current observations indicated that optimal Met level elevated muscle TOR mRNA abundance, the total and phosphorylation of TOR protein levels of on-growing grass carp. These results were consistent with reports in cobia Rachycentron canadum (56) , songpu mirror carp (57) and broiler (58) demonstrating that Met could increase TOR (mTOR) mRNA abundance in the muscle, as well as in grass carp (59) , showing that Met could advance the protein levels of total and phosphorylated TOR in the intestine. Also, we found that optimal Met level reduced the ratio of p-TOR Ser2448 /t-TOR in the current experiment, which was inconsistent with that in cobia (56) and turbot Scophthalmus maximus L. (60) .…”
Section: Methionine Promoted the Deposition Of Nutrients In The Muscle Of Fishsupporting
confidence: 93%
“…That result might be due to the fact that the effect of methionine on translation was greater than activation to TOR in our result, and similar result could be found in the study of bovine mammary epithelial cells (61) . In addition, optimal methionine level enhanced the protein level of p-S6K1 Ser389 and the ratio of p-S6K1 Ser389 : t-S6K1, while we failed to test any obvious change in the level of p-4E-BP1 Thr37/46 and the ratio of p-4E-BP1 Thr37/46 : t-4E-BP1, as the similar results in cobia (56) . Such a discrepancy between the phosphorylation status of these two proteins (S6 and 4E-BP1) has already been discovered in the muscle of rainbow trout (17) and in the liver of rats (62) in response to dietary methionine intake and highlights the complexity of the signaling network associated with the regulation of the activation of these translation initiation factors.…”
Section: Methionine Promoted the Deposition Of Nutrients In The Musclmentioning
confidence: 54%
“…These results indicate that the ability to regulate cell growth in vitro after Met treatment is related to the PI3K/Akt/TOR pathway, and these changes, which regulate cell growth, affect protein synthesis. We previously reported that dietary Met can affect the TOR pathway by stimulating the ASCT2 AA transporter and IGF‐I in cobia dorsal muscle (He et al, 2019). In this study, there were no significant differences in IGF‐I gene expression, indicating that Met might directly affect the PI3K/Akt/TOR pathway by stimulating ASCT2 in cobia muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot protocols were conducted based on our earlier article (He et al, 2019). Cells were lysed using Enhanced RIPA Lysis Buffer (Biosharp Biotech).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation